Pengaruh Viralitas Konten dan Fear of Missing Out terhadap Kunjungan Wisatawan di Gunung Sibayak, Sumatera Utara - M Chandra Wibowo; Raja Anan Nasution; Leo Benny; Rahma Dani Lubis (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
The development of social media has changed the behavior patterns of tourists in determining visiting decisions, particularly through the spread of viral content and the emergence of the Fear of Missing Out (FoMO) phenomenon. This study aims to determine the virality of content, fear of missing out, partially and simultaneously, on tourist visits. The population is Bang Fish product customers in Medan city, with a total of 160 respondents and a sampling of 157 respondents calculated using the Slovin formula. The data analysis technique used in this study is the structural equation modeling-partial least squares (SEM-PLS) analysis technique using SmartPLS 4 software. The results show that all variables have a positive and significant effect, with an R-square value of 0.151. Partially, Content Virality has a positive and significant effect on tourist visits, and Fear of Missing Out has a positive and significant effect on tourist visits. The findings of this study confirm that a digital marketing strategy based on viral content supported by an understanding of tourist psychological behavior is a strategic factor in increasing tourist visits, so it can be an important consideration for tourist destination managers in designing more effective and competitive promotional strategies. Keywords: Viral Content; Fear of Missing Out; Tourist Visit